Investigation of Sonic Under-expanded Jets Using Slotted Rectangular Mechanical Tabs - K. Anusindhiya; G. Vinayagamurthy; K. Sathish Kumar (Journal of Applied Fluid Mechanics)
Study on the behavior of jet flows are important for various reasons especially in the fields of aerospace, mechanical engineering, and environmental science. In aerospace engineering, understanding how jets behave can assist in increase / decrease thrust, decrease drag, improve fuel efficiency and reduce jet associated noise in aircraft engines and rockets. The flow control of jets is necessary for faster mixing and spreading, which can lead to much important aspects of noise reduction. Passive flow control of jets for various advantages like noise reduction, better mixing and thrust vector control is achieved by using mechanical slotted tabs. The effects of the slotted rectangular tabs are studied experimentally at different nozzle pressure ratios of 3, 4 and 5. The study involves the usage of three different novel configurations of rectangular slotted tabs for jet flow control. The Tabs A, B and C are designed with a blockage of 7.3% which are placed diametrically opposite to each other at the exit of a converging nozzle of 13 mm exit diameter. The centerline total pressure profiles, radial total pressure profiles and shadowgraph images for the tabbed cases are retrieved from the investigation and the results are compared with the free jet to study and visualize the jet mixing characteristics of the tabs. The results proved that tabs are found to be effective in enhancing the mixing and thereby reducing the acoustical characteristics of the jets. Tab C is seen to perform better in enhancing the mixing compared to other tabs with a percentage reduction of 89 %, 86 % and 84 % for the Nozzle Pressure Ratio (NPR) 3, 4 and 5 respectively.